Utilizing Madura's Cultural Heritage to Develop Critical Thinking Skills and Prevent Plagiarism in Scientific Writing - Harsono, Harsono; Amalia, Laili; Mukminin, Amirul; Raji, Moh.; Anam, Choirul (STAI Miftahul Ula Nganjuk, 2024)
Madurese local wisdom holds significant potential for fostering critical thinking skills and reducing plagiarism in scientific writing. This study explores the integration of Madurese cultural values into the learning process as a means to enrich academic practices. The research employs a qualitative approach, drawing data from interviews, observations, and literature analysis. The research focuses on Madurese cultural elements and their application within higher education settings. Results indicate that Madurese local wisdom serves as an effective tool for: (1) inspiring students to generate original and creative research ideas, (2) enhancing their capacity for critical and systematic analysis, and (3) cultivating academic integrity and reducing tendencies toward plagiarism. Additionally, incorporating local wisdom into education helps preserve cultural identity and builds student character. The study suggests the development of local wisdom-based curricula and stronger collaboration between academic institutions, cultural organizations, and the community to ensure sustainable integration of local cultural values in education.